Design And Build Door Security Using Fingerprint - Ujang Juhardi; Dedy Abdullah; Anisya Sonita; Khairus Syah Handrawijaya (Jurnal Komputer, Informasi dan Teknologi, 2023)
Today's technology has undergone many developments, with the development of these technologies can be put to good use. One technology that is currently being developed is in the field of security. Especially in the field of Biometrics because there are two functions, namely identification and verification. Biometrics have characteristics that are not lost, cannot be forgotten, and are not easily faked. Its existence is very close to humans, and one another is not the same so that uniqueness and security can be guaranteed. One of the biometrics that is easy to use is fingerprint, because this fingerprint pattern has high security and the fingerprint pattern is also easy to use. In increasing security, fingerprints can be applied as house door locks, because everyone's fingerprints are different so security will increase and it is not easy to access. The purpose of this tool is made so that it can be applied in the community, with this tool homeowners do not need to carry a key and only require fingerprints, so as to reduce the risk of crime that is rife in the community.